PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TEKNIK DUA TINGGAL DUA TAMU DISERTAI SPEED TEST TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 PANTI KABUPATEN PASAMAN - Nova Yulinda, Nova Yulinda; Rahmi, Rahmi; Aima, Zulfitri (Pendidikan Matematika, 2014)
ABSTRACT The background of this research was students compr ohension of mathematical concept still low, and when did on exercise in, learning process, the students often come to another friends. This research aim to know the students comprehension of matematical concept by applied cooperative learning technique two stay two stray with speed test, beetter then the students comprehension of mathematical concept by applied conventional learning at eight grade of SMPN 1 Panti. This research was an experimental. Population was eight grade of SMPN  1 Panti school year 2013/2014 VIII.4 as experimentall class and VIII.5 as control class. Instrument in this research was final test in essay from with reliability = 0,89. Based on data analisis know that both of class was homogeneous and have normal distribution at trust level 0,05. From the hypothesis test, got P-value was 0,004 it means small than so the hypothesiss accept. It can conlude thant students comprehension of mathematical concept by applied cooperative learning technique two stay two stray with speed test better than conventional learning at eight grade of SMPN 1 Panti 2013/2014